Diamond-like carbon coatings pin-on-disk wear testing - Strel'nitskij, V.E.; Vasylyev, V.V.; Makarov, V.B.; Lazarenko H.О. (Physics and Chemistry of Solid State, 2023)
The aim of this study is to investigate the wear resistance of diamond-like carbon (DLC) films and wear debris of polyethylene using pin-on-disc testing on two groups of CoCrMo discs with DLC coatings. DLC coatings deposited with use high productive vacuum-arc filtered plasma source in two regimes: with and without Ti interlayer on CoCrMo discs. The Orthopaedic Innovation Centre performed 2.5 million cycles (Mc) of POD testing on two groups of CoCrMo discs with DLC based on ASTM G99-17. The discs used were made of wrought low carbon alloy CoCrMo according to ASTM F1537. Wear performance of the PE pins against the DLC coated discs was determined and reported below. Lubricant samples were collected for each group after 0.5 and 2.5 Mc of testing, and used to characterize wear particles. All PE pins were assessed for damage features following 2.5 Mc of wear testing. The damage features identified included burnishing, scratching and grooving. The new process of DLC coating deposition from filtered vacuum arc plasma flows allows obtaining the stable DLC coating on the CoCrMo substrate. Thus, considering the low friction coefficient and the stable behavior of DLC such coating would be highly perspective for CoCrMo artificial joint implants.